Dental pulp stem cells retain mesenchymal phenotype despite differentiation toward retinal neuronal fate in vitro - Balasankar, Aishwarya; Chan, Shu-Yi Claire; Babu, Venkata Pakala Sudheer; Yam, Gary; Tin, Goh Bee; Singhal, Shweta (Frontiers in Medicine, 2022)
Dental pulp stem cells (DPSCs) are an easily accessible, heterogenous source of mesenchymal stem cells (MSCs) that are derived from the neural crest. Evidence suggests that they have neurotrophic qualities in their undifferentiated state and can also be differentiated into neuronal and retinal cell types. There is growing interest in using DPSCs in cell-based therapies to treat glaucoma and blinding retinal diseases. However, careful characterization of these cells is necessary as direct intravitreal and subretinal MSC transplantation is known to lead to deleterious glial reaction and fibrosis. In this study, we provide evidence for the mesenchymal-predominant nature of DPSCs and show that DPSCs maintain their mesenchymal phenotype despite upregulating mature retinal markers under retinal differentiation conditions. CD56, which was previously thought to be a specific marker of neural crest lineage, is robustly co-expressed with mesenchymal markers and may not be adequate for isolating a subpopulation of neural crest cells in DPSCs. Therefore, identification of more specific markers is required to elucidate the heterogeneity of the population and to successfully isolate a putative neural stem cell population before DPSCs can be used for retinal therapy.